2003
DOI: 10.1002/pola.10894
|View full text |Cite
|
Sign up to set email alerts
|

Living free‐radical polymerization (reversible addition–fragmentation chain transfer) of 6‐[4‐(4′‐methoxyphenyl)phenoxy]hexyl methacrylate: A route to architectural control of side‐chain liquid‐crystalline polymers

Abstract: Side‐chain liquid‐crystalline polymers of 6‐[4‐(4′‐methoxyphenyl)phenoxy]hexyl methacrylate with controlled molecular weights and narrow polydispersities were prepared via reversible addition–fragmentation chain transfer (RAFT) polymerization with 2‐(2‐cyanopropyl) dithiobenzoate as the RAFT agent. Differential scanning calorimetry studies showed that the polymers produced via the RAFT process had a narrower thermal stability range of the liquid‐crystalline mesophase than the polymers formed via conventional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…These include certain trithiocarbonates, xanthates, dithiocarbamates, and other compounds. The effectiveness of the RAFT agent depends on the monomer being polymerized and depends strongly on the properties of the free-radical leaving group R and the group Z which can be chosen to activate [44] (MMA), [44] AA [63] -7 [44] S, [14,44] (MMA) [6,44] -NC 8 [9,44] S, [9,14,44,46] AA, [6] MA, [44,64] NIPAM-XMA, [69] S-MAH, [70] MMA, [6,14,44,52] XMA, [65][66][67] EHMA-b-S, [68] EHMA-b-MMA-MA [68] VBz, [13,14] MMA, [68] BMA, [68] EHMA [68] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include certain trithiocarbonates, xanthates, dithiocarbamates, and other compounds. The effectiveness of the RAFT agent depends on the monomer being polymerized and depends strongly on the properties of the free-radical leaving group R and the group Z which can be chosen to activate [44] (MMA), [44] AA [63] -7 [44] S, [14,44] (MMA) [6,44] -NC 8 [9,44] S, [9,14,44,46] AA, [6] MA, [44,64] NIPAM-XMA, [69] S-MAH, [70] MMA, [6,14,44,52] XMA, [65][66][67] EHMA-b-S, [68] EHMA-b-MMA-MA [68] VBz, [13,14] MMA, [68] BMA, [68] EHMA [68] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…MMA [89] MMA-b-S [89] S 29 [44] MMA, [14,44] BA [14,44] [66] 3-[tris(trimethylsilyloxy)silyl]propyl methacrylate, [65] 6[4-(4 -methoxyphenyl)phenoxy]hexyl methacrylate, [67] N-hydroxysuccinimide methacrylate. [69] C Emulsion or miniemulsion experiments in italics.…”
mentioning
confidence: 99%
“…In addition, this approach can be used to control molecular weights (polymer chain length) and obtain block polymers. Recently, atom transfer radical polymerization (ATRP) [20] and reversible addition-fragmentation chain transfer (RAFT) [21] polymerization have been developed as examples of living radical polymerization. These polymerization reactions are useful for controlling the polymer chain length and realizing low polydispersity (M w /M n ).…”
Section: Addition Polymerization (Chain-growth Polymerization)mentioning
confidence: 99%
“…After this discovery, there have been many systematic studies on the effects of the spacer length on the thermal and physical properties of these SCLCPs. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been shown that increasing the spacer length while keeping the backbone and mesogenic groups constant has two effects: (i) the clearing temperature of the polymer increases and (ii) the entropy change associated with the clearing transition decreases. Most of the research work refers to polyacrylate, [33,34] polymethylacrylate, [35,36] polyurethane, [37] and polystyrene [38][39][40][41] backbones.…”
Section: Introductionmentioning
confidence: 99%